NGOs schools are promoting education for sustainable development in rural areas. (20th October 2022) - Saud, Muhammad; Ashfaq, Asia
ABSTRACT: During the last decade, provision of education has become a primary indicator for Sustainable Development as the key agenda under the United Nations SDGs. The essence of this goal is to enable upward socio-economic mobility and is a key to alleviate poverty, provide free primary and secondary education, access to technical and higher education, expand scholarships for developing countries, improve the infrastructure of schools, and ensure the literacy among men and women globally. The current research was conducted to investigate the role of NGOs in provision of education at primary level operating in rural communities in Pakistan. This cross-sectional study opted quantitative research design where purposive sampling technique was used to draw the sample from the population. The findings of the study conclude that NGOs are playing a vital role in providing educational facilities to the residents of rural communities where both communities and students are participating in multiple learning-based educational activities. The study also revealed that the parents of school-going children show a higher level of satisfaction from these formal educational institutes and agree that it is also supporting the local community to learn school management system by arranging close coordination between parents and teachers (PTA – parents-teacher association).